Determination of Gyro Frequency from Critical Frequency Measurements Over Parit Raja, Malaysia - Ahmad Faizal, Mohd Zain; Sabirin, Abdullah; Zeti Akma, Rhazali (2013)
The critical frequencies of the ionosphere are observed from ionograms to determine the gyro frequencies. The ionograms are obtained from the Parit Raja station using an ionosonde at latitude 1° 52' N and longitude 103° 48' E which is close to the geomagnetic equator at geographic latitude 5° N. Preliminary results show that the gyro frequencies obtained are between 0.2 MHz and 1.4 MHz.